Fixed-dose combination in management of type 2 diabetes mellitus: Expert opinion from an international panel - Sanjay Kalra; A K Das; G Priya; S Ghosh; R N Mehrotra; S Das; P Shah; S Bajaj; V Deshmukh; D Sanyal; S Chandrasekaran; D Khandelwal; et al. (Journal of Family Medicine and Primary Care, 2020)
Type 2 diabetes mellitus (T2DM) is a progressive disease with multifactorial etiology. The first-line therapy includes monotherapy (with metformin), which often fails to provide effective glycemic control, necessitating the addition of add-on therapy. In this regard, multiple single-dose agents formulated as a single-dose form called fixed-dose combinations (FDCs) have been evaluated for their safety, efficacy, and tolerability. The primary objective of this review is to develop practice-based expert group opinion on the current status and the causes of concern regarding the irrational use of FDCs, in Indian settings. After due discussions, the expert group analyzed the results from several clinical evidence in which various fixed combinations were used in T2DM management. The panel opined that FDCs (double or triple) improve patient adherence, reduce cost, and provide effective glycemic control and, thereby, play an important role in the management of T2DM. The expert group strongly recommended that the irrational metformin FDC's, banned by Indian government, should be stopped and could be achieved through active participation from the government, regulatory bodies, and health ministry, and through continuous education of primary care physicians and pharmacists. In T2DM management, FDCs play a crucial role in achieving glycemic targets effectively. However, understanding the difference between rational and irrational FDC combinations is necessary from the safety, efficacy, and tolerability perspective. In this regard, primary care physicians will have to use a multistep approach so that they can take informed decisions.